The Influence of Leadership Style and Organizational Culture on the Performance of Members of the Directorate of Water Patrol Sub-Directorate of the Water Police at the Headquarters of the Republic of Indonesia Police - Gara Hirayama Aprilandi; Yuni Pratikno; Jamal Hanaffy (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of leadership style on member performance, the influence of organizational culture on member performance, and the influence of both variables simultaneously on member performance at the Water Patrol Sub-Directorate of the Water Police at the Indonesian National Police Headquarters. The focus of this study is important because the performance of members of the Water Patrol Sub-Directorate is not only influenced by individual competence, but also depends heavily on the leadership patterns of leaders and the values of organizational culture that shape attitudes, behavior, and work ethic in carrying out operational tasks in water areas. This study uses a quantitative method with a survey approach to obtain numerical data that can be analyzed objectively. Primary data were collected through questionnaires, while qualitative data were obtained from respondents' statements and the results of limited discussions and interviews to complement the understanding of empirical conditions in the field. The study population was 104 members, with a sample of 82 respondents determined based on research criteria. Hypothesis testing was conducted using regression analysis through SPSS version 27. The results showed that leadership style (X1) and organizational culture (X2) had a positive and significant effect on member performance (Y) partially. In addition, both variables also have a simultaneous effect on member performance with an R-Square value of 0.416 or 41.6%, which means that performance variations can be explained by leadership style and organizational culture by 41.6%, while the remaining 58.4% is influenced by other factors outside the research model. This finding confirms that strengthening an effective leadership style and a positive organizational culture is an important strategy in improving the performance of members of the Water Patrol Sub-Directorate of the Indonesian National Police Headquarters Water Police